1999
DOI: 10.1038/sj.ejhg.5200286
|View full text |Cite
|
Sign up to set email alerts
|

SMN protein analysis in fibroblast, amniocyte and CVS cultures from spinal muscular atrophy patients and its relevance for diagnosis

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder caused by the homozygous absence of the telomeric copy of the survival motor neuron (SMNt) gene, due to deletion, gene conversion or point mutation. SMNt and its homologous centromeric copy (SMNc) encode the SMN protein, which is diffusely present in the cytoplasm and in dot-like structures, called gems, in the nucleus. We have studied the SMN protein in different cell cultures, including fibroblasts, amniocytes and CVS cells from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 26 publications
2
39
1
Order By: Relevance
“…Levels of FL-SMN in the type I sample were lower than levels from the type II and III samples, in agreement with previous studies. [29][30][31][32] Control samples (with two SMN1 and two SMN2 copies) showed an FL/D7 ratio of around 6-9, whereas SMA samples showed values ranging from 1.13 to 2.6. Interestingly, in the SMA patients, we found that lymphoblast ratios were slightly higher than those for fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of FL-SMN in the type I sample were lower than levels from the type II and III samples, in agreement with previous studies. [29][30][31][32] Control samples (with two SMN1 and two SMN2 copies) showed an FL/D7 ratio of around 6-9, whereas SMA samples showed values ranging from 1.13 to 2.6. Interestingly, in the SMA patients, we found that lymphoblast ratios were slightly higher than those for fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, SMN protein levels are reduced in spinal cord and cell cultures from SMA patients, and correlate inversely with phenotypic severity. [7][8][9] SMN2 copy number can also vary, and patients with high copy number often have a milder phenotype. [10][11][12] At present, there is no effective treatment for SMA.…”
Section: Introductionmentioning
confidence: 99%
“…RNA concentrations were determined using the GeneQuant II spectrophotometer (Pharmacia) and 2 mg RNA were used for first-strand cDNA synthesis, as described elsewhere. 11 Real time RT-PCR was performed using the ABI PRISM 7700 Sequence Detector System (Applied Biosystems, Foster City, CA, USA). SMN fl mRNA was amplified using a forward primer in SMN exon 6 (5 0 -GCT GAT GCT TTG GGA AGT ATG TTA-3 0 ) and a reverse primer in SMN exon 7 (5 0 -CAC CTT CCT TCT TTT TGA TTT TGT C-3 0 ); the sequence of the Taqman probe, localized in exon 6, was 5 0 FAM-TTT CAT GGT ACA TGA GTG GCT ATC ATA CTG GCT ATT AT-TAMRA 3 0 .…”
Section: Methodsmentioning
confidence: 99%
“…11 The antibodies were anti-SMN (dilution 1/5000, Transduction Laboratories), anti-b-tubulin (dilution 1/12 000) and anti-actin polyclonal antibody (dilution 1/2000, SigmaAldrich), anti-mouse horseradish peroxidase-conjugated (dilution 1/2000) and anti-rabbit horseradish peroxidaseconjugated (dilution 1/2000, Amersham Pharmacia Biosciences). Western blot quantification was performed as described; 11 SMN -actin -tubulin ratios were determined and normalized to untreated samples.…”
Section: Western Blot Analysismentioning
confidence: 99%